Spheroidal functions revisited: matrix evaluation and generating functions - Aquino, N.; Castaño, E.; Le, E.; -Koo. (Revista Mexicana de Física, 2002)
A matrix method to evaluate the angular spheroidal functions is presented as an alternative to the orthodox method.Plane waves are identified as generating functions of the spheroidal functions showing their explicit expansions.